2011
DOI: 10.3109/01443615.2011.633718
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and prolidase activity in women with uterine fibroids

Abstract: The aim of this study was to investigate oxidative stress markers and prolidase activity in serum and tissue samples of women with uterine fibroids, with further analysis on position and size. Lipid hydroperoxide, ceruloplasmin, catalase, arylesterase, free sulfhydryl group activity and prolidase activity levels were measured in fibroid tissue, myometrial tissue and serum of the same patients (n = 51), at the same time. Results show that ceruloplasmin, catalase, arylesterase, free sulfhydryl group and prolidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
(21 reference statements)
2
18
0
Order By: Relevance
“…Estrogen-induced ROS play important roles in cell transformation, cell proliferation, migration and invasion by increasing genomic instability and influencing redox sensitive transcription factors [21]. Although several reports have suggested the role of the oxidative stress in the development of uterine leiomyomas [2225], no study has investigated the markers of oxidative stress in the sera of patients. Such study could be useful to establish a relationship between the development of the tumor and to determine the pathways involved.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen-induced ROS play important roles in cell transformation, cell proliferation, migration and invasion by increasing genomic instability and influencing redox sensitive transcription factors [21]. Although several reports have suggested the role of the oxidative stress in the development of uterine leiomyomas [2225], no study has investigated the markers of oxidative stress in the sera of patients. Such study could be useful to establish a relationship between the development of the tumor and to determine the pathways involved.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] This study gathered further evidence to support a role of oxidative stress in the pathophysiology of fibroids. We have demonstrated the overexpression of NOX in fibroid as compared to normal myometrial tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…But the free radicals are regulated by superoxide dismutase also released into the uterus (Vural et al, 2012). Since Bianchi et al (2001) and Mandavilli et al (2002) reported that higher level of hydrogen peroxide was generated from cells that have mitochondrial DNA mutation during tumor development and progression, the deregulated level of TPP observed in our leiomyoma patients could be due to enhanced free radical generation in the macrophage infiltrated myoma tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In a normal uterus, there is expression of superoxide dismutase that regulates the constantly generated reactive oxygen species, which serve as a local protector of the uterus against infectious agents (Vural et al, 2012). But in a leiomyoma tissue, activation of infiltrating macrophages generate more free radicals, secrete interleukin-6 and several growth hormones including epidermal growth factor, transforming growth factor-α, transforming growth factor-β, heparin-binding epidermal growth factor, acidic fibroblast growth factor, basic fibroblast growth factor, vascular endothelial growth factor, insulin-like growth factor, platelet-derived growth factor, activin and myostatin in myometrium and in leiomyomas (Ciarmela et al, 2011).…”
Section: Introductionmentioning
confidence: 99%